Perceptions and Disjunctions in Urban Space - Carter, Matthew James (Auckland University of Technology, 2009)
In this studio based visual arts project I am exploring through representational painting and compositing, perceptions, conjunctions and disjunctions in space and time in the urban environment. My approach situates the stranger as the phenomenological self, the perceptual being, at the centre of the research who explores the spatio-psychology of the city in the light of contradictory philosophies that move between seeing the city as a place of social malaise to seeing it as a malleable space for each individual within it.
Keywords: Urban space; Placelessness; Psycho-spatial; Disjunctions; Space and time; Aerial view